New guidelines for hr management in the context of the development of the green economy (MMIT Proceedings, 2025)
The article analyzes the directions of HR management transformation in the context of the green economy, examines the HR management functions aimed at supporting sustainable practices, and provides examples of successful integration of "green" initiatives into corporate policy.